THE CASE OF HERPETIC ECZEMA IN A CHILD WITH CONGENITAL ICHTHYOSIS AND ATOPIC DERMATITIS - A. S. Stadnikova; O. B. Tamrazova; T. A. Chebotareva (LLC "Diagnostics and Vaccines", 2017)
The case of the development of herpetic eczema (Kaposi's eczema) is presented against the background of congenital ichthyosis and atopic dermatitis. It has been shown that the presence of atopic diseases such as allergic rhinitis and pollinosis, sensitization to many common allergens, and a positive family history of atopic dermatitis are factors of a more severe course of Kaposi's eczema. The presented clinical observation of the child with Kaposi's eczema showed that early diagnosis and timely initiated complex  therapy are the determining factors of a favorable prognosis of the disease.